Dietary Zinc Intake and Inflammatory Bowel Disease in the French NutriNet-Santé Cohort. (August 2020) - Vasseur, Pauline; Dugelay, Emmanuelle; Benamouzig, Robert; Savoye, Guillaume; Hercberg, Serge; Touvier, Mathilde; Hugot, Jean-Pierre; Julia, Chantal; Lan, Annaïg; Buscail, Camille
Abstract : INTRODUCTION: This study aimed to assess the association between incident Crohn's disease (CD) or incident ulcerative colitis (UC) and dietary zinc intake. METHODS: NutriNet-Santé cohort's participants who completed at least three 24-hour dietary records were included and incident CD or UC cases were identified. Multivariable Poisson models were performed to assess associations between tertiles of zinc intake and CD or UC. RESULTS: Among the 105, 832 participants, 27 reported incident CD and 48 reported incident UC. The relative risks of CD decreased with dietary zinc intakes. Compared with participants with the lowest tertile of zinc intake, the relative risks for CD were 0.60 (95% confidence interval [0.22–1.66]) and 0.12 (95% confidence interval [0.02–0.73]) for the second and the highest tertiles, respectively ( P trend = 0.02). No significant association was observed for UC. DISCUSSION: Dietary zinc intake was inversely associated with incident CD.